2022
DOI: 10.3389/fmicb.2022.868575
|View full text |Cite
|
Sign up to set email alerts
|

Coxiella Endosymbiont of Rhipicephalus microplus Modulates Tick Physiology With a Major Impact in Blood Feeding Capacity

Abstract: In the past decade, metagenomics studies exploring tick microbiota have revealed widespread interactions between bacteria and arthropods, including symbiotic interactions. Functional studies showed that obligate endosymbionts contribute to tick biology, affecting reproductive fitness and molting. Understanding the molecular basis of the interaction between ticks and their mutualist endosymbionts may help to develop control methods based on microbiome manipulation. Previously, we showed that Rhipicephalus micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 97 publications
(141 reference statements)
1
4
0
Order By: Relevance
“…The results obtained of the ticks’ microbiome are consistent with previous studies in which bacteria of the family Coxiellaceae, encompassing Coxiella burnetii and Coxiella -like endosymbionts (CLEs), have been detected ( Wu-Chuang et al, 2021 ; Guizzo et al, 2022b ). Coxiella burnetii causes Q fever in humans and coxiellosis in animals, this distinction between C. burnetii and the Coxiella -like endosymbionts (CLEs) in ticks is problematic besides the latter are non-infectious to vertebrate hosts but are necessary for the health of these arthropods ( Duron et al, 2015 ; Brenner et al, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…The results obtained of the ticks’ microbiome are consistent with previous studies in which bacteria of the family Coxiellaceae, encompassing Coxiella burnetii and Coxiella -like endosymbionts (CLEs), have been detected ( Wu-Chuang et al, 2021 ; Guizzo et al, 2022b ). Coxiella burnetii causes Q fever in humans and coxiellosis in animals, this distinction between C. burnetii and the Coxiella -like endosymbionts (CLEs) in ticks is problematic besides the latter are non-infectious to vertebrate hosts but are necessary for the health of these arthropods ( Duron et al, 2015 ; Brenner et al, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…was eliminated ( Ben-Yosef et al., 2020 ). In R. microplus , the comparative transcriptomic analysis of Coxiella -free nymphs revealed a substantial under-expression of tick transcripts involved in their blood-feeding capacity ( Guizzo et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Members of the families Coxiellaceae and Francisellaceae with endosymbionts of the genera CLE and FLE were observed in R. microplus and D. nitens as previously described [ 25 ] in wild ticks from India, horse ticks, and livestock ticks from China [ 26 ]. Functional studies have shown that CLE contributes to tick biology by affecting reproductive fitness and molting [ 27 ]. Many Coxiella species have been recorded as endosymbionts in ticks; for example, in Amblyomma , their presence in the salivary glands alters the transmission of Ehrlichia chaffeensis [ 28 ].…”
Section: Discussionmentioning
confidence: 99%